Accelerating marker assisted selection for disease resistance using SNP enabled competitive Allele Specific PCR (KASP) markers in rubber (Hevea brasiliensis) - Roy C.B; Anu K; Goonetilleke S.N; Limiya J; Madhavan J; Mather D.E; Saha T (PLACROSYM XXIII. Climate Resilient Technologies for Sustainability of Plantation Crops, 6-8 March 2019, Central Coffee Research Institute, Chikkamangaluru, Karnataka, India, Abstracts, p. 10.)
Three major destructive fungal diseases of rubber tree causing significant loss to rubber production are the abnormal leaf fall disease caused by Phytophthora spp, Corynespora leaf disease caused by Corynespora cassiicola and Colletotrichum leaf disease caused by Colletotrichum spp. Management of these diseases is mainly with the use of chemical fungicides, which is environmentally unsafe. Due to the lengthy selection process involved inconventional breeding, molecular breeding tools like marker-assisted selection (MAS) can be employed in rubber. Single nucleotide polymorphisms (SNPs) such as insertions, deletions and basepair substitutions are more advantageous than other molecular markers. The biallelic nature of SNPs as well as their abundance in a genome provides flexibility in choosing SNPs at the desired loci.Competitive allele-specific PCR (KASP) is a genotyping technology for screening of trait-specific SNP markers. One hundred and eighty two F! progeny of an interspecific cross between H. brasiliensis and H. benthamiana were evaluated for resistance ot Phytophthora, Colletotrichum and Corynespora diseases. Eighty six of these were used for the construction of linkage map for each parent using genotyping-by-sequencing (GBS) data derived from DArTsequencing. The linkage maps had 18 linkage groups (LGs), reflecting the haploid chromosome number of Hevea (n=18) and detected significant QTLs for Phytophthora (LGs 1 and 8) and Corynespora (LGa 1, 12 and 13) on H. benthamiana and for Colletotrichum on both H. benthamiana (LGs 10, 12 and 18) and H. brasiliensis (LGs 5, 6 and 11) maps. Allele specific marker assays using KASP TM technology were developed using fifty GBS tag pairs that were mapped close proximity to each QTL on relevant LGs adn assayed on 182 progeny population, providing more reliable genetic maps with higher resolution. This study has revealed the potential use of SNP markers in combination with KASP genotyping assay for MAS for disease resistance in rubber.
Keywords: Allele Specific PCR; Colletotrichum; Corynespora; Disease management; Fungal disease; Phytophthora